Negotiating The Post-Truth Power of Prophecy: A Sequel of Prince Local in The Old-Order – Dipanegara’s 1 Great Java War (1825-1830) - Annysa Endriastuti; Eko Kusumo (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2018)
This article is not to negotiate the arena of accepting one to another, dichotomy between the body and soul, but to see how acts of discipline put one in touch with realities, or a Reality, not discernible in mere ordinary life experience. Brown i added that ‘deepening a relation to that Reality by humanizing the world in which one lives is what life is all about’. At the same time this article is also to discuss how the negotiation of the eschatological vision of prince’s life is prophetically inclined. It is by first giving respect to this classical Javanese Babad Dipanegara literature as one of the Indonesian cultural and spiritual heritage illuminating the way of how prince life deepened via this integrality; integration prince’s reality with a Reality is what matters within his leadership assistance. Respecting this local literary means to reveal the unforgettable Java War impetus that involved Islamic values being integrated into contemporary Javanese and Indonesian identity; besides, it is to particularly bring about the Javanese locals’ characteristic of their intangible culture that today nation’s development level recently requires – a sample of how prince’s heroic, spiritualistic trait had managed to cope with realities and above all, witnessed a Reality. It is of important to note how this prophecy in the setting of Javanese culture be incorporated, depicted, administered through the embodiment of prince’s way of life, his noble philosophy, and his religious culmination. It is by discussing this classical Javanese literature –macapat 2 Babad Dipanegara that this prophecy be addressed itself to its most tendentious mystery.